Analysis and design of analogue class D amplifier output stages - Kwek, Lawrence Boon Kheng (2008)
It is well established that Class D audio amplifiers have higher power efficiency compared to classical linear amplifiers (Class A, Class B and Class AB) due to the fact that the transistors in their output stage operate either in the cut-off region or in the triode region. As the output stage typically dissipates the highest power of all circuit blocks in audio amplifiers, the overall power efficiency of amplifiers largely depends on the design of the output stage. The optimization of the output stage based on CMOS (embodying the p-channel-cum-nchannel inverter) has been reported in literature. These output stages are limited only to low voltage (~5V) applications due to the low breakdown voltage of CMOS. In this dissertation, we investigate the power dissipation mechanisms of the High Voltage MOS (HVMOS) output stage in half bridge configuration (the half bridge can be easily extended to the full bridge) and the Double-diffused MOS (DMOS) output stage in full bridge configuration, and apply protection circuits to the output stages for higher voltage (~20V) applications. We derive analytical expressions to determine their power efficiencies and establish a methodology to optimize the channel width of the output stages for optimum power efficiency. We also propose a small non-overlapping logic circuit to reduce the possibility of short-circuit current. The derived expressions depict the parameters that affect power efficiency, and are insightful to designers to design the output stage for optimum power efficiency in view of IC area. The analytical results are verified against Cadence (Spectre) computer simulations for both DMOS and HVMOS, and on the basis of measurements on an IC for DMOS. The DMOS output stage is shown to offer higher power efficiency than the HVMOS output stage due to its lower on-resistance and lower capacitance.